A critical race theory inquiry into service learning pedagogy in historically white institutions - Morapedi, Kgomotso (My University, 2021)
The global trend of policy borrowing has shaped the landscape of Higher Education policies in South Africa. The implementation of an American model of service learning (SL) as the curriculum and pedagogical strategy to Community Engagement (CE) could reflect and continue a whiteness pedagogy. Whiteness is understood as not an attack on white people, but rather as being a socially constructed power and privilege; which tends to ignore race, class, gender and their intersections. Studies in America have shown that SL perpetuates this whiteness pedagogy, as it is embedded in the discourse, institutional practices and pedagogy which can lead to further injustices and a miseducation of students when working with communities. Which is problematic in South African institutions given the racially segregated past and need for the decolonisation of pedagogy and curriculum. This study adopted whiteness studies and critical race theory (CRT) frameworks. Both frameworks provide means to inquire on the extent to which the American model of SL has influenced the practice and conceptualisation of the South African SL (Eramus , 2011). Given, the lack of benefit for communities from SL and the difference between the rhetoric and reality of SL as shown in the literature. This study aimed to answer the question of which ways might the South African SL reproduce a whiteness pedagogy? By investigating how race, class, gender and their intersections shaped SL pedagogy, course design, student’s experiences and reflections. Data was collected through document analysis of the schools of Social Work and Nursing course materials, student’s journal reflections and semi-structured interviews with students and lecturers. Both schools were selected as SL is an important part in students’ undergraduate studies. Furthermore, SL is arguably for both schools a course that bridges the gap between theory and practice and enables students to apply their knowledge in real community contexts. The study drew on a critical realist paradigm and on Archer’s analytical dualism given the racialised, classed and gendered stratification of reality that shapes SL pedagogy. Findings from the study show that the field of SL has certain aspects that reproduce a whiteness pedagogy which influenced how SL was conceptualised and understood at the research site. While, there other aspects of SL tackle issues of power and privilege in SL this was evident in how students were taught to work with FIC and the surrounding communities. The study found that Asset-based theories and community assessments were used to ensured that communities are not viewed in a deficient view but rather as partners in solving the problems facing them. The study concludes by giving recommendations on how to tackle the issues identified in the study
A research report submitted to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirement for the degree Master of Education (by coursework and research report) in the discipline of Educational Leadership and Policy Studies (ELPS), 2021